Same or different? the CEO labour market in China's public listed companies - Bryson, Alex; Forth, John; Zhou, Minghai (Wiley, 2014)
Using linked employer–employee data for all China's public listed firms over the period 2001–10, we find top executive compensation exhibits many of the traits familiar in the Western literature, although sometimes in a more muted way, and with some clear exceptions. We also find a role for managerial power in executive pay setting which may reflect the recency of the stock market and regulations underpinning corporate governance. Nevertheless, there appear to be some elements of executive compensation which transcend national economic, political and cultural differences. The implication is that the Western model is not as idiosyncratic as critics suggest.